2015
DOI: 10.1007/s10661-015-4747-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution system water age can create premise plumbing corrosion hotspots

Abstract: Cumulative changes in chemical and biological properties associated with higher "water age" in distribution systems may impact water corrosivity and regulatory compliance with lead and copper action levels. The purpose of this study was to examine the effects of water age and chemistry on corrosivity of various downstream premise plumbing pipe materials and configurations using a combination of controlled laboratory studies and a field survey. Examination of lead pipe, copper pipe with lead solder, and leaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 74 publications
(63 reference statements)
3
18
2
Order By: Relevance
“…; Masters et al . ,b), similar to blood Pb levels in exposed children in mining areas of Nigeria (Thurtle et al . ).…”
Section: Discussionsupporting
confidence: 73%
“…; Masters et al . ,b), similar to blood Pb levels in exposed children in mining areas of Nigeria (Thurtle et al . ).…”
Section: Discussionsupporting
confidence: 73%
“…The Washington DC, USA Lead Crisis (2001–2004) first demonstrated that the standard water Pb avoidance flushing guidance was inadequate during AL exceedances, and that flushing for only 15–30 s would directly expose consumers to hazards of water that had been held within the lead service lines [ 15 , 18 ]. A decade of follow up research has since confirmed that flushing protocols which reduce exposure in a given home, are highly dependent on variables that are difficult or impossible to control, including, but not limited to the length, configuration, material, condition and disturbance of service lines or plumbing, water use patterns, spatial changes in chemical and microbiological water quality within a given distribution system; and type of Pb released (particulates vs. dissolved) [ 2 , 3 , 11 , 14 , 15 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In light of the evidence challenging the efficacy of flushing under different conditions, the EPA identified a need to further evaluate flushing [ 38 ] and revised the Lead and Copper Rule and Consumer Confidence Report Rule to allow utilities to modify the required flush time recommendations if they determine longer flush times are needed [ 17 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many water quality problems in Water Distribution Networks (WDNs) can be associated with high water residence time in the system, known also as water age. Indeed, high water age affects several physical, biological and chemical aspects, contributing to the accumulation of sediments in pipes, corrosion, undesirable odours and stimulation of chemical reactions (Association, American Water Works 2002;Machell and Boxall 2014;Machell et al 2009;Masters et al 2015). Besides, chlorine residual concentration decreases with age, impacting its efficiency as a purifier.…”
Section: Introductionmentioning
confidence: 99%